An assessment of the implementation of Batho Pele Principles in the Department of Agriculture in Limpopo Province of South Africa. - Swana, Maphuti Enett (My University, 2008)
The Batho Pele principles provide a framework about how public services should be provided for improving the efficiency and effectiveness of the Public Service. Adherence to these principles will guarantee the provision of excellent services that meet the people’s needs and expectations, enhance customer satisfaction, while upholding the government’s promise that access to decent public services is no longer a privilege to be enjoyed by a few, but the rightful expectation of all citizens. From the literature review, it was evident that improved public service delivery depends on several aspects ranging from Human Resource Development to performance measurement and accountability. The need for improving efficiency and effectiveness of the Public Service is emphasized through the various pieces of legislation. Interviews and questionnaires were used to gather data and to get an understanding of data from the point of view of the participants. Analysis of collected data revealed that there is an average compliance of 51, 5% to the principles. Batho Pele principles should be incorporated in the performance contracts of all employees in the department so that periodically performance against them is assessed and ultimately all employees will become Batho Pele champions.
Thesis (MPA) --University of Limpopo, 2008.
Keywords: Batho Pele Principles